The Need for Early Referral: Characteristics of Children and Adolescents Who Are Overweight and Obese Attending a Multidisciplinary Weight Management Service - Jacqueline L. Walker; Rebecca Malley; Robyn Littlewood; Sandra Capra (MDPI AG, 2017)
There is a need to examine the issue of childhood obesity from a systems perspective. This study aimed to describe the baseline characteristics of children attending pediatric multidisciplinary weight management services and understand how this information will inform future service delivery. A total of 51 children and adolescents who were overweight and obese (27 male) and aged between two and 16 years participated. Body size measures such as body mass index (BMI) and body fat percentage were collected. Participants and their parents/guardians also completed questionnaires on dietary intake, behaviors and habits, physical activity and health-related quality of life. A total of 72% of participants were classified as morbidly obese. Adolescents had significantly lower scores for overall diet, physical activity and particular health-related quality of life scores. No significant correlations were found between BMI z-scores and diet, physical activity and health-related quality of life. In adolescents, correlations were detected between dietary scores and health-related quality of life. Results confirm the need to critically examine the current context to adapt and tailor interventions to individual circumstances, and when combined with focused referral, triaging and screening processes, should assist in delivering the right care at the right time.